How (often) do voters change their consideration sets?. (February 2019) - Rekker, Roderik; Rosema, Martin
Abstract: The consideration set model posits that in multi-party elections voters decide in two stages. We expect that in the consideration stage, when voters select viable options, ideological proximity is a key determinant, while in the choice stage election-specific factors become particularly important. This would imply that consideration sets are rather stable and that changes in voting preferences occur mainly within ideologically coherent consideration sets. This study examines both claims by analyzing panel survey data from Sweden and the Netherlands. Consideration sets were indeed rather stable, more so than voting intentions. After one year, voters still considered the same party in 81% of cases and only 13% of respondents shifted between ideological camps. This indicates that voters changed electoral preferences primarily within the boundaries of relatively stable consideration sets and ideological camps. These findings help to understand how elections can be volatile, despite the strong impact of highly stable ideological orientations.